2021
DOI: 10.1016/j.jbc.2021.101204
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of NADH:ubiquinone oxidoreductase (complex I) content in biological samples

Abstract: Impairments in mitochondrial energy metabolism have been implicated in human genetic diseases associated with mitochondrial and nuclear DNA mutations, neurodegenerative and cardiovascular disorders, diabetes, and aging. Alteration in mitochondrial complex I structure and activity has been shown to play a key role in Parkinson's disease and ischemia/reperfusion tissue injury, but significant difficulty remains in assessing the content of this enzyme complex in a given sample. The present study introduces a new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 90 publications
1
12
0
Order By: Relevance
“…It strongly suggested that the mechanism of inactivation of the brain enzyme is in fact redox-dependent dissociation of tightly bound complex I flavin. In order to directly identify the mechanism of complex I inactivation, we developed a method to accurately determine only complex I-associated FMN in mitochondrial preparations [ 39 ]. A typical Coomassie-stained hrCN PAGE gel of DDM-solubilized intact mitochondria from the brain and heart is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It strongly suggested that the mechanism of inactivation of the brain enzyme is in fact redox-dependent dissociation of tightly bound complex I flavin. In order to directly identify the mechanism of complex I inactivation, we developed a method to accurately determine only complex I-associated FMN in mitochondrial preparations [ 39 ]. A typical Coomassie-stained hrCN PAGE gel of DDM-solubilized intact mitochondria from the brain and heart is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…After denaturation of the native protein by SDS [ 39 ], we observed two major flavin-containing bands corresponding to mitochondrial α-ketoglutarate dehydrogenase (αKGDHC) and complex I ( Fig. 3 A, lanes 4–5, ∼1200 kDa and 850 kDa bands, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations